2018
DOI: 10.4103/sjg.sjg_6_18
|View full text |Cite
|
Sign up to set email alerts
|

Mirizzi's syndrome: A scoring system for preoperative diagnosis

Abstract: Background/Aim:Mirizzi's syndrome (MS) is an unusual complication of gallstone disease and occurs in approximately 1% of patients with cholelithiasis. Majority of cases are not identified preoperatively, despite the availability of modern imaging techniques. A preoperative diagnosis can forewarn the operating surgeon and avoid bile duct injuries in cases of complicated cholecystitis. A preoperative scoring system helpful and hence, we aim to devise a scoring system based on clinical, biochemical, and imaging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…CT proved to be approximately as sensitive as the US in our review, but it was repeatedly pointed out that its main advantage is differentiating MS from malignant strictures [31,32]. MS is listed as one of the diseases mimicking cholangiocarcinoma, but the fact us that the coexistence of MS and GBC is no less important [33,[39][40][41]. Prasad et al reported that patients with MS and simultaneous GBC were a decade older than and had twice as long a history of symptoms as patients who only had MS alone [33].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…CT proved to be approximately as sensitive as the US in our review, but it was repeatedly pointed out that its main advantage is differentiating MS from malignant strictures [31,32]. MS is listed as one of the diseases mimicking cholangiocarcinoma, but the fact us that the coexistence of MS and GBC is no less important [33,[39][40][41]. Prasad et al reported that patients with MS and simultaneous GBC were a decade older than and had twice as long a history of symptoms as patients who only had MS alone [33].…”
Section: Discussionmentioning
confidence: 76%
“…There were 32 patients with MS. The authors further evaluated the patients according to the scoring system they had developed and conducted a statistical analysis which showed that a score of 3 or more out of 10 has a sensitivity of 90.6% and specificity of 78.1% in predicting the Mirizzi syndrome [41].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, sensitivity and specificity data for the detection of cholecystoduodenal fistulas by ERCP, MRCP, CT, and ultrasound have not been reported. However, the sensitivity and specificity data for the detection of related conditions such as gallstone ileus and Mirizzi syndrome (another type of internal biliary fistula, cholecystocholedochal fistula, is classified as type 2 Mirizzi syndrome [12,13]) have been reported. CT has been reported to be up to 93% sensitive and 100% specific for the detection of gallstone ileus [14], and ERCP has been reported to have a mean sensitivity of 76.2% for Mirizzi syndrome [15][16][17]; indeed, a 2013 study suggested a 100% sensitivity rate of ERCP for Mirizzi syndrome [18].…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is a complication of prolonged cholelithiasis, with prevalence from 0.05% to 2.7% among patients with calculi of the gallbladder. It presents a spectrum that varies from extrinsic compression of the CHD to the presence of cholecystobiliary fistula [ 2 ]. Usually, this syndrome is associated with cholecystobiliary fistula (cholecystohepatic or cholecystocholedochal), as in type II or III according to Csendes et al classification, but the presence of an internal biliary fistula as cholecystoduodenal, cholecystocolonic or cholecystogastric requires the most recent Beltran Classification, in which Type V has been introduced to describe the cholecystoenteric fistula, with or without gallstone ileus [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%